The Application of Speech Therapy to Overcome Speech Delays in Early Childhood in Inclusive Education - Ibnu Imam Al Ayyubi; Eko Prayetno; Brilliant Windy Khairunnisa (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2025)
This study aims to evaluate the effectiveness of speech therapy in overcoming speech delays in early childhood. This study uses an experimental design with a control group, consisting of two classes: an experimental class that receives speech therapy and a control class that follows conventional methods. This study uses a quantitative approach with an experimental method, using a quasi-experimental design, specifically a non-equivalent control group design. The research population consisted of all students from both institutions. Statistical analysis was performed using SPSS software, and the findings were interpreted in relation to the research hypothesis and theoretical framework. The results showed that at the pretest stage, there was no significant difference between the two groups, and similarly, at the posttest stage, there was no significant difference between the experimental class and the control class. These comparable results show that the effectiveness of the application depends on the implementation and involvement of the teacher. This study highlights the need for further research to explore additional factors that may influence the effectiveness of speech therapy in overcoming speech delays in early childhood.